2011
DOI: 10.1371/journal.pone.0020208
|View full text |Cite
|
Sign up to set email alerts
|

A Template-Dependent Dislocation Mechanism Potentiates K65R Reverse Transcriptase Mutation Development in Subtype C Variants of HIV-1

Abstract: Numerous studies have suggested that the K65R reverse transcriptase (RT) mutation develops more readily in subtype C than subtype B HIV-1. We recently showed that this discrepancy lies partly in the subtype C template coding sequence that predisposes RT to pause at the site of K65R mutagenesis. However, the mechanism underlying this observation and the elevated rates of K65R development remained unknown. Here, we report that DNA synthesis performed with subtype C templates consistently produced more K65R-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 80 publications
3
25
0
Order By: Relevance
“…Additionally, low abundance of K65R have been detected by UDPS in ART-naïve non-B subtypes and correlated with virological failure [5]. The predominance of K65R in subtype C can be explained by a template pausing molecular mechanism that facilitates the selection of K65R in the KKK motif at codons 64, 65, 66 of the RT [3032], and has been suggested that this characteristic of the KKK motif can lead to PCR induced K65R [33]. However, a recent UDPS study were controls of different percentages of K65R mutation were included and the theoretical and observed values of K65R plasmid dilutions were similar (100%:94%, 5%:2.30% and 1%:0.90%), indicates that the frequencies of K65R obtained by UDPS are reasonably accurate [34].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, low abundance of K65R have been detected by UDPS in ART-naïve non-B subtypes and correlated with virological failure [5]. The predominance of K65R in subtype C can be explained by a template pausing molecular mechanism that facilitates the selection of K65R in the KKK motif at codons 64, 65, 66 of the RT [3032], and has been suggested that this characteristic of the KKK motif can lead to PCR induced K65R [33]. However, a recent UDPS study were controls of different percentages of K65R mutation were included and the theoretical and observed values of K65R plasmid dilutions were similar (100%:94%, 5%:2.30% and 1%:0.90%), indicates that the frequencies of K65R obtained by UDPS are reasonably accurate [34].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to reverse transcriptase pausing during the synthesis of double-stranded DNA from the single-stranded DNA intermediate template, a process that is template-specific but independent of the reverse transcriptase enzyme [14, 15, 148]. Subsequent misalignment of the subtype C template and primer leads to the AAG to AGG change responsible for the K65R mutation [149] (Figure 2). On the contrary, subtype B templates are prone to frequent pausing at codon 67, facilitating the generation of mutation D67N and TAMs instead of K65R (Figure 2, Table 1) [148, 150, 151].…”
Section: Development Of Resistance To Antiretroviral Therapy Amongmentioning
confidence: 99%
“…Interestingly, NVP-containing regimens have been associated with an increased risk of K65R detection [27,28], but the mechanism has not yet been described. Overall, while HIV-1 subtype C has an increased risk of K65R under drug pressure[27,29], the extent to which these K65R mutations are from reverse transcription error in vitro or in vivo, is unclear.…”
Section: Discussionmentioning
confidence: 99%